THE EFFICIENCY OF THE COMPETENCE-ORIENTED TEACHING METHOD AT THE CLINICAL DEPARTMENTS OF I. HORBACHEVSKY TERNOPIL NATIONAL MEDICAL UNIVERSITY - Shved, M. І.; Heryak, S. М.; Martynyuk, L. P.; Susla, О. B.; Yastremska, І. О. (Здобутки клінічної і експериментальної медицини, 2023)
Among researchers, there is no established view on the structure of professional competence of future specialists in general and future doctors in particular, regarding the types of competences that should be laid as its basis. This situation served as the basis for conducting an analysis of the effectiveness of various communicative educational methods for improving professional training of master's students at the university's clinical departments. The aim – to analyze the effectiveness of various teaching methods for the formation of professional competence of future doctors in key and subject competencies in emergency medical care. Results. Communicative competence is a dynamic combination of knowledge and practical skills, ways of thinking, professional, worldview, social qualities, moral and ethical values, which determines the ability of a person (student) to successfully carry out professional and further educational activities and is the result of learning at a certain level of education. The formation of the communicative competence of master's students is achieved thanks to the effective interaction of the teacher and the student (communication, exchange of knowledge, practice of abilities and skills), professional and personal qualities of the teacher, which are manifested through analytical perceptive, motivational-communicative, professionally-oriented and tactical-psychological communicative skills in solving professional tasks and individual properties of the subject of professional and pedagogical activity, necessary and sufficient for mastering communicative skills at the normatively determined level. To form the professional competence of future doctors in key and subject competencies in emergency medical care, the teachers of the clinical departments use a complex of interactive teaching methods based on the principles of a participatory-interactive approach. Such teaching methods include the method of educational discussion, game teaching methods, dialogue method, method of individual and group projects, as well as independent work of master's students. Conclusions. In order to achieve high communicative and professional competence of the future master's doctor in the specialty of emergency medical care, the teachers of the clinical departments of the university use such participatory and interactive teaching methods as the educational discussion method, game teaching methods, the dialogue method, the method of individual and group projects, as well as the method of independent works of master's students. The effectiveness of using each educational method depended on the individual characteristics of the personality of the teacher and the student, their basic level of training and motivation.